Factors influencing long‐term efficacy and tolerability of bosutinib in chronic phase chronic myeloid leukaemia resistant or intolerant to imatinib. (4th November 2015) - Brümmendorf, Tim H.; Cortes, Jorge E.; Khoury, Hanna J.; Kantarjian, Hagop M.; Kim, Dong‐Wook; Schafhausen, Philippe; Conlan, Maureen G.; Shapiro, Mark; Turnbull, Kathleen; Leip, Eric; Gambacorti‐Passerini, Carlo; Lipton, Jeff H.
Summary: The dual SRC/ABL1 tyrosine kinase inhibitor bosutinib is indicated for adults with Ph+ chronic myeloid leukaemia (CML) resistant/intolerant to prior therapy. This analysis of an ongoing phase 1/2 study (NCT00261846) assessed effects of baseline patient characteristics on long‐term efficacy and safety of bosutinib 500 mg/day in adults with imatinib (IM)‐resistant (IM‐R; n = 196)/IM‐intolerant (IM‐I; n = 90) chronic phase (CP) CML. Median treatment duration was 24·8 months (median follow‐up, 43·6 months). Cumulative major cytogenetic response (MCyR) rate [95% confidence interval (CI)], was 59% (53–65%); Kaplan‐Meier (KM) probability of maintaining MCyR at 4 years was 75% (66–81%). Cumulative incidence of on‐treatment progression/death at 4 years was 19% (95% CI, 15–24%); KM 2‐year overall survival was 91% (87–94%). Significant baseline predictors of both MCyR and complete cytogenetic response (newly attained/maintained from baseline) at 3 and 6 months included prior IM cytogenetic response, baseline MCyR, prior interferon therapy and <6 months duration from diagnosis to IM treatment initiation and no interferon treatment before IM. The most common adverse event (AE) was diarrhoea (86%). Baseline bosutinib‐sensitive BCR‐ABL1 mutation was the only significant predictor of grade 3/4 diarrhoea; no significant predictors were identified for liver‐related AEs. Bosutinib demonstrates durable efficacy and manageable toxicity in IM‐R/IM‐I CP‐CML patients.